AN ANALYSIS OF PAKISTAN’S CLIMATIC FACTORS AFFECTING MARINE FISH PRODUCTION - SHAHZAD, SM (Biological and Clinical Sciences Research Journal, 2023)
A lot of study has been done on how climate change impacts farming. But there aren’t many studies in Pakistan that look at how climate change changes the number of fish that can be caught in the real world. This study’s main goal is to look at the effects of climate change on fish in the sea around Pakistan from 1990 to 2020. It was given to us by the World Development Indicators. This study used the autoregressive distributed lag (ARDL) model to examine how the link between CO2 emissions, weather, rainfall, and sea fish production changes over time. Using the autoregressive distributed lag (ARDL) method to cointegration, a strong link was found between rains and the number of fish caught. To determine if rainfall has a statistically significant effect on sea fish production in the short term, we used the coefficient for rainfall (β = 5738.02) and found that it does. In the long run, it makes a difference at the 1% level of importance. Both changes in temperature and CO2 pollution hurt fish production a lot, according to the study. This is true in the short as well as in the long term. Researchers found that it would be helpful for lawmakers to make national policies that are better for adapting to climate change and supporting long-term control of marine fishing. Pakistan’s fishing business should do a lot of research and development to find marine fish species that can live in places with a lot of CO2 and high temperatures.